Artificial intelligence : ethical, social, and security impacts for the present and the future - Mehan, Julie E. (IT Governance Publishing Ltd, 2022)
A global perspective on AI. This book will provide a global perspective on AI and the challenges it represents, and will focus on the digital ethics surrounding AI technology.